Dinitrogen Emissions Dominate Nitrogen Gas Emissions From Soils With Low Oxygen Availability in a Moist Tropical Forest. Issue 1 (19th January 2023) - Almaraz, Maya; Groffman, Peter M.; Silver, Whendee L.; Hall, Steven J.; Lin, Yang; O'Connell, Christine; Porder, Stephen
Abstract: Lowland tropical forest soils are relatively N rich and are the largest global source of N2 O (a powerful greenhouse gas) to the atmosphere. Despite the importance of tropical N cycling, there have been few direct measurements of N2 (an inert gas that can serve as an alternate fate for N2 O) in tropical soils, limiting our ability to characterize N budgets, manage soils to reduce N2 O production, or predict the future role that N limitation to primary productivity will play in buffering against climate change. We collected soils from across macro‐ and micro‐topographic gradients that have previously been shown to differ in O2 availability and trace gas emissions. We then incubated these soils under oxic and anoxic headspaces to explore the relative effect of soil location versus transient redox conditions. No matter where the soils came from, or what headspace O2 was used in the incubation, N2 emissions dominated the flux of N gas losses. In the macrotopography plots, production of N2 and N2 O were higher in low O2 valleys than on more aerated ridges and slopes. In the microtopography plots, N2 emissions from plots with lower mean soil O2 (5%–10%) were greater than in plots with higher mean soil O2 (10%–20%). We estimate an N gas flux of ∼37 kg N/ha/yr from this forest, 99% as N2 . These results suggest that N2 fluxes may have been systematically underestimated in these landscapes, and that the measurements we present call for a reevaluation of the N budgets in lowland tropical forest ecosystems. Plain Language Summary: Nitrogen is a macronutrient that limits plant productivity in much of the world. Tropical forests have a relatively large number of nitrogen fixing species, they tend to cycle nitrogen in excess of plant demand. This excess nitrogen is released into the environment in either dissolved or gaseous forms. Wet, warm, and organic matter‐rich soils of tropical forests result in a hot spot for denitrification; a process that removes nitrogen from soils and converts in into either nitric oxide, nitrous oxide, or dinitrogen gas. Because dinitrogen makes up 80% of earth's atmosphere, it's difficult to measure a small flux coming off the soil. This knowledge gap has resulted in a limited understanding of soil nitrogen cycling in tropical ecosystems. Because soil moisture can influence denitrification, we tested how wet points in the landscape influence emissions of dinitrogen gas. We found that wetter low points in the landscape result in the highest dinitrogen fluxes, and that dinitrogen dominated nitrogen gas emissions from these soils. We used these data to estimate dinitrogen emissions for this forest and generated a larger value than previously calculated. Such results suggest a need to integrate dinitrogen measurements into studies of nitrogen cycling in tropical forest soils. Key Points: Dinitrogen dominated nitrogen gas emissions from tropical forest soils Valleys were hot spots of nitrogen emissions in this tropical landscape Dinitrogen fluxes may change our understanding of nitrogen budgets in this forest